Pelatihan dan Pendampingan Aplikasi SIAPIK Pada Pelaku Usaha UMKM Pukat Teri Sihombing di Kecamatan Medan Belawan - Sinaga, Ernita Rumenta (Ikatan Cendekiawan Muda Akuntansi, 2023)
Training and mentoring of the SIAPIK application was carried out for Sihombing Teri Trawl MSME business actors in the Medan Belawan area to help record financial data and use the SIAPIK application. MSMEs play an important role in the Indonesian economy, but many MSMEs do not understand the importance of recording financial data. This mentoring action strategy includes preparation and guidance on using the SIAPIK application. The results of the initial survey showed that the business actors of Pukat Teri Sihombing MSMEs did not understand about recording financial information and using the SIAPIK application. However, after training and mentoring, it is expected that the business actors of Pukat Teri Sihombing MSMEs will really want to use the SIAPIK application to work on recording financial information for the businesses they run.